Optimalisasi Peran Kader Posyandu Dalam Pelayanan Stunting - nurhayati, siti (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2023)
Stunting is a health problem in which children experience chronic malnutrition caused by inadequate nutritional intake over a long period of time. The Asian Development Bank, (2022) states that the prevalence of stunting in children under the age of 5 is around 31.8% in Indonesia. The data also places Indonesia in 10th place in Southeast Asia. Based on the results of the Indonesian Nutritional Status Survey (SSGI), the prevalence of stunting under five in Indonesia will reach 21.6% in 2022. This research uses the Literature Review method by looking for references that are relevant to the problem. The aim is to find out how to optimize the role of posyandu cadres in dealing with stunting in Indonesia. The results obtained were 9 articles that met the inclusion and exclusion criteria for further analysis. Based on the analysis of the article, it was found that the role of posyandu cadres can be optimized by providing training and debriefing to increase knowledge and skills, especially in dealing with at-risk families with stunting children.